PENGARUH SUHU PENGERINGAN TERHADAP IMOBILISASI LOGAM BERAT PADA BETON GEOPOLIMER YANG DISINTESIS DARI ABU LAYANG BATUBARA DAN SAMPAH KACA - Nur Ruwantari, Ira; Trihadiningrum, Yulinah; Wilujeng, Susi Agustina (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Geopolymer can be an alternative to Portland cement by using industrial and household waste as more environmentally friendly raw materials. This study investigated the effect of curing temperature on the ability of fly ash and glass waste-based geopolymer paste to immobilize heavy metals. Two compositions were used, 100% fly ash (FA) and a mixture of 50% fly ash and 50% glass waste (FA:SG). The binder in this composition was activated with 10 M NaOH and Na₂SiO₃ in a molar ratio of 1:2. The specimens were molded into cubes with dimensions of 5×5×5 cm³ and cured at temperatures of 30, 90, and 120°C for 24 hours before being stored at room temperature for 28 days. Leaching tests were carried out using the Toxicity Characteristic Leaching Procedure (TCLP) method with reference to USEPA 1311 for Pb, Cr, Cu, and Zn. The results showed that the curing temperature of 90°C with a composition of 50:50 produced the lowest metal leaching, namely B: 0.78 mg/L, Pb: 0.078 mg/L, Cd: 0.03; Cr6+: 0.02 mg/L, Cu: 0.019 mg/L, and Hg: 0.0007 mg/L, Zn: 2.71 mg/L. All of these values ​​are far below the TCLP-A quality standard threshold in PP No. 22 of 2021. These results prove that geopolymerization is effective in stabilizing heavy metals and has strong potential as a sustainable waste-based construction material.